Dampak sosial industrilisasi tambak udang terhadap lingkungan di Desa Andulang Kabupaten Sumenep - Yetti Hidayatillah (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
Industrialization is a process of socio-economic change that transforms the livelihoods of agrarian societies into industrial societies. Shrimp farming industry Andulang village 20 years ago has been a pond, for permit development of shrimp farming industrialisasi in Andulang village already have permission from Integrated Licensing Service Agency. Among the benefits with the industrialization of shrimp ponds in Andulang Village is creating jobs for economic needs. Nevertheless, there is a social problem that is felt by the community around the industry, namely environmental pollution. First, land contamination of productive agricultural land becomes unproductive. Second, water pollution that is against the sea to itch and smell. Third, air pollution around the shrimp ponds that cause unpleasant odors. KeywordsSocial Impact, Industrialization, Shrimp Pond http://dx.doi.org/10.17977/um022v2i22017p073